On The Whole-Cell Cell Saccharomyces Cerevisiae Biotransformation Of Ketoisophorone At Different Substrate Concentrations - Mohd Razif, Illya Syafiqah (Universiti Sains Malaysia, 2018)
Baker’s yeast type II has been utilized in this study as a biocatalyst to investigate the reduction of 2, 6, 6-trimethylcyclohex--2-ENE-1,4-Dione (ketoisophorone) into a useful chiral intermediates as well as for its valuable product that is (4R,6R) -4-hydroxy-2,6,6-trimethylcyclohexanone or in short (4R, 6R) -actinol. Five different substrate of ketoisophorone has been introduced at different culture in order to investigate the effect of the cofactor regeneration and the time courses of ketoisophorone to produce corresponding intermediates of 2,6,6-trimethylcyclohexane-1,4-dione [(6R)-levodione] and 4-hydroxy-2,6,6- trimethylcyclohex-2-ene-1-one [(4S)-phorenol] and the main product (R)-hydroxy-2,2,6-trimethylcycloheanone [(4R,6R)-actinol] on the whole- cell Saccharomyces cerevisiae. The cofactor availability and stability has been investigated by using ultraviolet-visible and it was found that at 2.0 g/L of substrate concentration the cofactor availability is the lowest as the nutrient-limiting of glucose. There is no effect of substrate concentration towards cell inhibition from 0.2 g/L to 2.0 g/L. Gas chromatography was used to analyse the substrate, intermediates; (6R)-levodione and (4S)-phorenol and main product (4R, 6R)-actinol. The concentration of (6R)-levodione has higher concentration compared to (4S)-phorenol due to the competition of coenzymes and higher rate of carbon-carbon double bond reduction compared to the reaction rate of carbonyl reduction.